Performance of Loaded Thermal Storage Unit with a Commercial Phase Change Materials based on Energy and Exergy Analysis - Olimat, Abdullah Nasrallh; Awad, Ahmad S; AL-Gathain, Faisal M.; Shaban, Nabil Abo (International Journal of Renewable Energy Development, 2017)
This work presents an energy/exergy analysis to investige performance of thermal storage unit which loaded with a commercial phase change material (Plus ICE H190). The influence of fluid parameters on the energy/exergy effectiveness was examined. The temporal changes of the energy and exergy rate and performace of the storage unit are obtainedÂ  in the results. Latent heat principle is considered an efficient method to gain a higher effectiveness of system from an energy and exergy aspects. The fluid mass flow rate during charging and discharging periods were 2.50 kg/min and 1.26 kg/min, respectively. The results showed a significant increase of thermal resistance on the thermal storage unit performance. Fluid and phase change material show significant temperature difference on the rate of energy/exergy quantites and the time of melting or soldification. Ther results indicated that the average rate of energy and exergy were 1.3 kW and 0.54 kW, respectively. Wheras, energy and exergyÂ  average rate during discarging periods were 1.1 kW and 0.31 kW, respectively. Also, the global rate during the experimetal periods were about 84% and 54%, respectively.Article History: Received July 6th 2017; Received in revised form September 15th 2017; Accepted 25th Sept 2017; Available onlineHow to Cite This Article: Olimat, A.N., Awad, A.S., Al-Gathain, F.M., and Shaban, N.A.. (2017) Performance of Loaded Thermal Storage Unit With A Commercial Phase Change Materials Based on Energy and Exergy Analysis. International Journal of Renewable Energy Development, 6(3),283-290.https://doi.org/10.14710/ijred.6.3.283-290